2022
DOI: 10.1007/s00209-021-02959-5
|View full text |Cite
|
Sign up to set email alerts
|

Invariants for trees of non-archimedean polynomials and skeleta of superelliptic curves

Abstract: In this paper we generalize the j-invariant criterion for the semistable reduction type of an elliptic curve to superelliptic curves X given by $$y^{n}=f(x)$$ y n = f ( x ) . We first define a set of tropical invariants for f(x) using symmetrized Plücker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In [10], this result was extended to arbitrary complete non-archimedean fields and an easier proof was given. This paper in turn was based on [11], where skeleta of general superelliptic curves are studied. In the latter, it was shown that one can recover the skeleton from tropicalizations of certain functions in the coefficients of f (x).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In [10], this result was extended to arbitrary complete non-archimedean fields and an easier proof was given. This paper in turn was based on [11], where skeleta of general superelliptic curves are studied. In the latter, it was shown that one can recover the skeleton from tropicalizations of certain functions in the coefficients of f (x).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…We refer to M 0,n as the moduli space of smooth n-marked curves of genus zero. There is a natural compactification of this space, given by replacing smooth curves by stable curves in (11). We denote the corresponding scheme by M 0,n .…”
Section: Moduli Of Tropical Curvesmentioning
confidence: 99%
“…In [Hel21b], this result was extended to arbitrary complete non-archimedean fields and an easier proof was given. This paper in turn was based on [Hel22], where skeleta of general superelliptic curves are studied. In the latter, it was shown that one can recover the skeleton from tropicalizations of certain functions in the coefficients of f (x).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…We now recall from [Hel22] how the reduction type of a Picard curve y 3 (x, z) = q(x, z) can be recovered from the (4, 1)-marked tree of (q, ). We refer the reader to [Hel22, Section 1.2] for the definition of the reduction type of a curve.…”
Section: Proof Of Theoremmentioning
confidence: 99%
See 1 more Smart Citation